The New book of knowledge : Vol. 13 (New York : Grolier, 1973)
A twenty-volume edition illustrated with maps, pictograms, and photographs, mostly in color. Entries are written by qualified specialists at reading levels ranging from ages six to twelve. Every volume is separately indexed with cross references to pertinent information found in other volumes of the set.
First published in 1912 under title: The Book of knowledge.
Keywords: Children's encyclopedias and dictionaries; Encyclopedias and dictionaries